Latent infection of Vigna unguiculata with seed-borne bean common mosaic virus modulates plant growth and may contribute to mutualistic symbiosis between the virus and host plant - Takahashi, Hideki; Xu, Nan; Kanayama, Yoshinori; Tabara, Midori; Takeda, Atsushi; Fukuhara, Toshiyuki; Miyashita, Shuhei (Frontiers in Microbiology, 2025)
In evaluating the germination and growth of the seed resources of 322 cultivars of cowpea (Vigna unguiculata), we found the development of yellow symptoms on 50% of the cotyledons of 10 cultivars. RNA-Seq analysis of total RNA extracted from symptomatic cotyledons indicated that the 10 cultivars were infected with the bean common mosaic virus (Potyvirus phaseovulgaris, BCMV), which is a member of the family Potyviridae and able to seed-transmit to progeny plants. One of the BCMV isolates identified in the 10 cultivars was BCMV(Vu06), which was infected with cultivar #6. During the growth of BCMV(Vu06)-infected cowpea plants, there were no systemic symptoms in newly developing leaves, but the virus coat protein was detected in both leaves and flowers. Thus, the cowpea cultivar #6 plant was latently infected with BCMV(Vu06). There was no significant difference in the dry matter weight of the above-ground parts of the plant between BCMV(Vu06)-latently infected and non-infected plants. However, BCMV(Vu06)-latently infected plants had late flower and bud formation and longer life but slightly lower seed yield than the non-infected plants. The 1,000-seed weight and germination frequency of the seeds harvested from infected plants were the same as those of non-infected plants. Taken together, latent infection of cultivar #6 with BCMV(Vu6) modulates the balance between vegetative and reproductive plant growth and the longer lifespan of BCMV(Vu06)-latently infected plants may provide an advantage for its survivability over generations. BCMV(Vu06) and cowpea cultivar #6 might have established a mutual symbiotic relationship during their interaction.